Topical Interest and Degree of Involvement of Bilingual Editors in Wikipedia - Kim, Soo Young; Oh, Alice (Proceedings of the International AAAI Conference on Web and Social Media, 2021)
Language reveals a lot of information about its speakers. Speakers of one language usually share common cultural habits or regional characteristics, and their similarities become more obvious within the context where there are multiple languages in use. We focus on studying bilingual users of Wikipedia, one of the largest multilingual user-generated content platforms. In Wikipedia, we can observe the patterns in the English edition, where users of multiple languages come together to express their thoughts and interests in the common language of English. To understand the specific topics edited by bilingual users, we analyze them in terms of revision counts, topics, and country names. We find that bilingual users are generally interested in more local topics, and their language is highly related with their topics. Also, we observe that the topical diversity decreases with the proportion of English edits, and more concentrates on topics related with countries and cultures.